INFLUENCE OF CAMPUS FACILITIES, IMPLEMENTATION OF USR PROGRAM (UNIVERCIT SOCIAL RESPONSIBILITY), HUMAN RESOURCES DEVELOPMENT ON CAMPUS IMAGE WITH MEDIA RELATIONS AS VARIABLE INVERVENING - Andri Kurniawan; Martha Suhardiyah; Subakir Subakir (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
Complete facilities in the educational institutions also encourage the realization of a conducive learning process, no exception for universities as a place to develop scientific knowledge. The college has a social, economic and environmental responsibility to be the mindset and culture of the organization at any business venture. The university's social responsibility as a responsibility for the activities and behaviors of the institutions is influenced and impacted by society. These responsibilities require management practices that eliminate negative impacts and support sustainable development. This research uses a sample of this study as much as 103 people consist of structural officials, and the manager of Hima Progdi the Environment University PGRI Adi Buana Surabaya. The results of this study showed that there is a partial positive influence among Varianel campus facilities, the Univercity Social Responsibility (USR), on media relation, while the HUMAN development variables are not on the media relation and image of the campus and there is a correlation between campus facilities variables, Univercity Social Responsibility (USR), human resources development, with media relation and campus image